2014
DOI: 10.3109/10428194.2014.904508
|View full text |Cite
|
Sign up to set email alerts
|

Prospective single-center study of chronic myeloid leukemia in chronic phase: switching from branded imatinib to a copy drug and back

Abstract: Imatinib (Glivec(®)/Gleevec(®)) has shown long-term efficacy and safety in randomized trials. No large-scale studies have prospectively assessed the benefit-risk profile of an imatinib copy drug. We prospectively evaluated the response of patients with chronic myeloid leukemia in chronic phase in one institution. Patients with a complete hematologic response (n = 126) switched from branded imatinib to an imatinib copy drug. Subsequently, all patients switched back to the branded imatinib. Many patients in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The article was first published in February 2014, sharing the accurate and evidencebased data about the efficacy and safety data of generic imatinib in CML available at that time point. 1 Generics of imatinib entered the drug market in Turkey in August 2012, and shortly after the present article 1 was published, our group has published a couple of articles, sharing our-''Cerrahpas¸a'' experience 2-4 regarding this issue, as some other authors 5,6 in 2014.…”
mentioning
confidence: 92%
“…The article was first published in February 2014, sharing the accurate and evidencebased data about the efficacy and safety data of generic imatinib in CML available at that time point. 1 Generics of imatinib entered the drug market in Turkey in August 2012, and shortly after the present article 1 was published, our group has published a couple of articles, sharing our-''Cerrahpas¸a'' experience 2-4 regarding this issue, as some other authors 5,6 in 2014.…”
mentioning
confidence: 92%
“…In the literature, some authors suggested that original molecule is superior to generics. 14,15 In a study which was conducted with 30 patients, generic TKI was used as first line therapy and resulted with 90% CHR and 46.7% molecular response rate. 16 On the other hand, a One of the clinical limitation of the reports which suggest generic TKIs are inferior that these studies involve relatively small number of cases or they are just case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Generics of IM have been approved in many countries including Canada, India, Iraq, Colombia and Turkey [3,6,11,12]. The entry of the IM generics into the Turkish drug market has resulted in substantial price reductions since August 2012.…”
mentioning
confidence: 99%
“…Alwan et al [11] evaluated the HRs in patients with chronic phase-CML in a prospective study setting where patients had to switch from the original molecule to a generic IM (Imatib, Cipla) for at least 9 months and then switch back to the original IM. Dose escalations to 600 or 800 mg original IM once daily or changing to nilotinib 400 mg twice daily were allowed if patients failed to show optimal response to 400 mg IM after switching from the generic drug.…”
mentioning
confidence: 99%